Penerapan Model Pembelajaran Mind Map untuk Meningkatkan Pemahaman Materi Peta Siswa Kelas V SD - Naili Azkiya Sari; Reza Fandi Tyasari; Syailin Nichla Choirin Attalina (Jurnal Pendidikan Dirgantara, 2025)
. This Classroom Action Research aims to improve students' understanding of map material in social science lessons using the Mind Map learning model. The research was conducted at SD Negeri 1 Damarjati with fifth-grade students as the subjects. The research consisted of two cycles, each comprising planning, action, observation, and reflection stages. The methods used to collect data were tests, observations, interviews, and documentation. In the pre-cycle, students demonstrated a limited understanding of map material, as reflected in both their test scores and classroom participation. The findings revealed a notable increase in students' comprehension after the implementation of the Mind Map learning model. The average class score rose from 56.1 in the pre-cycle to 70.8 in Cycle I, and further increased to 84.5 in Cycle II. Moreover, the percentage of students achieving the minimum mastery criteria (KKM) also improved significantly—from 30% in the pre-cycle to 56.6% in Cycle I, and then to 90% in Cycle II. The improvement was not only in academic achievement but also in learning enthusiasm, student engagement, and the ability to recall and connect concepts. The Mind Map learning model helped students better visualize the relationship between different elements of the subject matter, which enhanced both individual and group learning. Additionally, classroom observations indicated that students became more active in discussions and showed better collaboration with peers. These results indicate that the implementation of the Mind Map learning model not only enhances cognitive engagement and visual comprehension but also fosters students’ participation and collaborative learning environments. Thus, it can be concluded that the Mind Map learning model is an effective, student-centered method to improve understanding of map material in elementary schools.